SPECIFIC RELIEF OF THE INTERNAL SURFACE SIDES UPPER SAGITTAL SINUSES OF THE DURA MATER BRAIN OF THE HUMAN - Черно, В.С.; Шепітько, В.І.; Бенюх, А.В.; Хилько, Ю.К. (World of Medicine and Biology, 2012)
Present morphological specific formation of intra-axillary of the upper sagittal sinuses of the dura mater brain of the human.